小屁孩日记第12册双语版 / xiǎo pì hái rì jì dì 12 cè shuāng yǔ bǎn / the getaway ebook - Kinney, Jeff (Diary of a Wimpy Kid, 2022)
为了摆脱假期的压力，Heffley 一家决定离开小镇去度假，而不是在家庆祝圣诞节。 但最初的无压力假期变成了一场噩梦。 To escape the stress of the holidays, the Heffleys decide to get out of town and go to a resort instead of celebrating Christmas at home. But what's billed as a stress-free vacation becomes a holiday nightmare.